Determinants of Teachers’ Organizational Commitment: The Role of Transformational Leadership, Self-Efficacy, and Job Satisfaction in Islamic Elementary Schools - Masrifah, Masrifah; Hidayat, Rais; Laihad, Griet Helena (Jurnal Paedagogy, 2025)
This study aims to examine the direct and indirect influence of transformational leadership, self-efficacy, and job satisfaction on teachers’ organizational commitment in Integrated Islamic Elementary Schools. Using a quantitative approach with the path analysis method, data were collected through a structured questionnaire measured on a 5-point Likert scale from 145 permanent foundation teachers (GTY) in Cibinong District, West Java Province, Indonesia, selected by proportional random sampling based on the Slovin formula. The instrument, developed from established theoretical constructs, was validated using Pearson Product-Moment correlation and tested for reliability with Cronbach’s Alpha, both confirming its accuracy and internal consistency. The results showed that job satisfaction had the strongest direct influence on teachers’ organizational commitment (β = 0.665; t = 16.420), compared to transformational leadership (β = 0.123) and self-efficacy (β = 0.164). In addition, transformational leadership and self-efficacy also have an indirect effect on organizational commitment through job satisfaction as a mediating variable. These findings affirm the importance of job satisfaction as a strategic factor in increasing teacher commitment in Islamic-based schools.